2011
DOI: 10.1063/1.3553839
|View full text |Cite
|
Sign up to set email alerts
|

Transient operation of the relativistic S-band magnetron with radial output

Abstract: The influence of the time-varying accelerating voltage and electromagnetic waves reflected from the output window of the antenna on the operation of a relativistic S-band magnetron with radial output is analyzed. It is shown that within the range of radiation frequencies generated by the magnetron, the antenna with the dielectric window and feed waveguide can be considered as a resonant load. Depending on the phase relations between the reflected electromagnetic waves and those traveling in the magnetron, mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It had been shown 4-8 that ILMs and SILMs are able to fix the operating frequency and phase, and essentially decrease the noise of the radiation. 9,10 show that the efficiency of the relativistic S-band magnetron can be significantly (up to 40%) increased when part of the radiated electromagnetic power is reflected into the magnetron cavity. This effect, to our knowledge, has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown 4-8 that ILMs and SILMs are able to fix the operating frequency and phase, and essentially decrease the noise of the radiation. 9,10 show that the efficiency of the relativistic S-band magnetron can be significantly (up to 40%) increased when part of the radiated electromagnetic power is reflected into the magnetron cavity. This effect, to our knowledge, has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant influence of the structural aspect ratio, α in selecting the mode of operation. Generally accepted [13] criteria is that small α devices (α < 1) tend to operate in single mode at π-mode frequency. The tendency to operate in multimode grows at higher α-values, and large-α devices can simultaneously support a number of different modes including π and 2π, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[11][12][13] Earlier research [14][15][16] of high-impedance (!50 X) RMs with radial microwave power output showed its high microwave power efficiency ($60%). Recently, [17][18][19][20][21] we demonstrated the increase in the microwave pulse duration up to $150 ns with the same high efficiency. However, for long (!100 ns) microwave pulses, RMs have some specific features not typical to conventional magnetrons.…”
mentioning
confidence: 98%
“…However, for long (!100 ns) microwave pulses, RMs have some specific features not typical to conventional magnetrons. Namely, the power of the microwave pulses and the frequency vary significantly with very small changes in the reflection coefficient of the microwaves from the load; 19 the microwave generation continues despite a significant decrease (to a half) in the applied voltage and the microwave frequency drifts (by $10%) relative to their value at the beginning of the oscillations. [20][21][22] In addition, in RM experiments 10 with multi-channel microwave output, the power radiated from the open resonant cavities adjacent to closed cavities was found to depend on the direction of the external axial magnetic field.…”
mentioning
confidence: 99%
See 1 more Smart Citation